A COMPARISON OF TWO DESLORATADINE PREPARATIONS’ (SOLUTION AND SYRUP) EFFECTIVENESS AND TOLERABILITY IN ATOPIC DERMATITIS TREATMENT IN CHILDREN OF EARLY AGE - I. V. Makarova; O. V. Trusova; O. V. Zhiglinskaya; E. A. Medvedeva; L. A. Galenko (Вопросы современной педиатрии)
Objective: The aim of our study was to compare the effectiveness and tolerability of desloratadine solution vs syrup formulation in children with atopic dermatitis. Methods: Children of the 1st group received desloratadine solution and children of the 2nd group received desloratadine syrup 1,25 mg o.d. in complex atopic dermatitis treatment including also topical therapy, diet and emollients, for 4 weeks. Results: 40 children 12 to 24 months of age with no more than 45 points on the SCORAD scale were included in open-label comparative randomized trial. Subjective atopic dermatitis symptoms, itch and sleep disturbance due to itching, most rapidly decreased after treatment beginning. At the end of the study, itch completely resolved in most patients. Other symptoms such as erythema, papules and skin edema, excoriations, crusts and exudation also decreased. The SCORAD index decreased from 35.9 to 3.45 points and from 34.9 to 3.45 points in the 1st and the 2nd treatment groups, respectively. Treatment tolerability was good in both groups. Conclusion: Desloratadine application in atopic dermatitis complex treatment is effective in children and gives possibility to reach a disease remission in most patients. We did not reveal significant differences in two desloratadine preparations’ (solution and syrup) effectiveness and tolerability.